Peran Hukum Dalam Kasus Suap Menyuap Yang Terjadi Di Keolahragaan Indonesia - Fatimatuz Zahro; Berliana Ananta Putri; Mirza Nabila Putri (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The practice of bribery and manipulation in the sports environment has become a serious problem that shakes the principles of integrity and fairness in the competitive arena. Starting from match-fixing scandals to acts of corruption in decision-making, this phenomenon not only disrupts match results, but also undermines public confidence in fairness in sport. It is important to recognize that sport is not just about physical competition on the field, but also about moral and ethical principles that must be upheld. Law has a crucial role in establishing the framework that regulates behavior in and around sport. Cases of bribery and manipulation in the field of sports have become a disturbing problem over the last few decades. These corrupt practices threaten the integrity of sports competitions and undermine the fundamental values ​​upheld in society. In bribery cases, there are usually 3 elements, namely the bribe giver, the bribe recipient and the bribe item. Those who give bribes are those who give money, items of high value or in any form whose value can be calculated to someone with the aim of making the person given the item of value want to do or not do something in accordance with what the bribe giver wants. A bribe recipient is a person who receives something of value from the bribe giver to do or not do something. A bribe is something given by the bribe giver to the bribe recipient.